PENDIDIKAN HOLISTIK DALAM ISLAM: STUDI TERHADAP IQ, EQ, DAN SQ - Mariani, Mariani (UIN Antasari Banjarmasin, 2021)
Abstract: This article reveals holistic education in Islam, namely the study of IQ (Intellegent Quotient or intellectual intelligence), EQ (Emotional Quotient or emotional intelligence), and SQ (Spiritual Quotient or spiritual intelligence) in Islam. The holistic education paradigm is a way of looking at education as a whole, not partial, limited, and rigid. This holistic education paradigm can certainly be seen as in line with the world view of Islamic education. Al-Qur'an and al-Hadith explicitly discuss aqal, qalbu, and fuad as the center of IQ, EQ, and SQ showing that Islam gives equal appreciation to the three intelligence systems. The relationship between the three can be said to need and complement each other, because Islam places equal emphasis on